2014
DOI: 10.11648/j.crj.20140201.12
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and Postmenopausal Obesity: the Risk Factors in this Relationship

Abstract: The prevalence of obesity is increasing rapidly in both the developed and the developing countries, thus contributing to the occurrence of other diseases, e.g. hypertension, diabetes and breast cancer. Breast cancer involves a multifactorial process in which the surrounding microenvironment is known to be of great importance in the development and progression of the disease. Thus, adipose tissue, due to its immunological, metabolic and endocrine properties, may play a crucial role in the onset and progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To date, these mechanisms are not yet completely understood: however three hormonal systems are hypothesized to explain this association, such as insulin and insulin-like growth factors (IGFs), especially IGF binding protein-1 factor (IGF-1); sex hormones; and adipokines (Travis and Key, 2003;Kaaks et al, 2005;Renehan et al, 2008;Mazur-Roszak et al, 2010;Vecchia et al, 2011;Alegre et al, 2013;De Pergola and Silvestris, 2013;Minatoya et al, 2013;Brown, 2013a, 2013b;Barp et al, 2014). General and central obesity is positive correlated with insulin resistance followed by elevated its concentration in serum.…”
Section: Overweight Obesity and Bc Riskmentioning
confidence: 99%
“…To date, these mechanisms are not yet completely understood: however three hormonal systems are hypothesized to explain this association, such as insulin and insulin-like growth factors (IGFs), especially IGF binding protein-1 factor (IGF-1); sex hormones; and adipokines (Travis and Key, 2003;Kaaks et al, 2005;Renehan et al, 2008;Mazur-Roszak et al, 2010;Vecchia et al, 2011;Alegre et al, 2013;De Pergola and Silvestris, 2013;Minatoya et al, 2013;Brown, 2013a, 2013b;Barp et al, 2014). General and central obesity is positive correlated with insulin resistance followed by elevated its concentration in serum.…”
Section: Overweight Obesity and Bc Riskmentioning
confidence: 99%
“…In obesity there is an unbalanced maturation, with higher quantities of preadipocytes, and consequently, a greater secretion of pro inflammatory cytokines. Therefore, the increase in the liberation of pro inflammatory cytokines resulting from obesity is a great factor of risk for the development of breast cancer in women in the post menopause state [88].…”
Section: Overtraining Riskmentioning
confidence: 99%
“…At menopause, these enzymes are found mainly in adipose tissue and liver, and use as intermediates the testosterone or androstenedione in the conversion of oestradiol [28]. It is observed that aromatase activity is increased in obesity management and, as a result, there is an increase in estradiol formation and increased risk of tumors [37]. It is known that testosterone may influence the risk for breast cancer directly, or indirectly (in the conversion to estradiol).…”
Section: Drugs and Hrtmentioning
confidence: 99%